Building a Better Cambodia - Neall, Beatrice; Nang ChanYeema (Phnom Penh, Cambodia Seventh-Day Adventist Mission, 1997)
A collection of proverbs and short stories from Solomon, Buddha, Jesus, Lincoln, Gandhi, and others, that show how to find joy in life through service to others.
Keywords: Adult Nonfiction